2022
DOI: 10.1002/jcla.24420
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and gut–microbiota–brain axis: A narrative review

Abstract: Introduction Obesity is a major health problem that is associated with many physiological and mental disorders, such as diabetes, stroke, and depression. Gut microbiota has been affirmed to interact with various organs, including the brain. Intestinal microbiota and their metabolites might target the brain directly via vagal stimulation or indirectly through immune‐neuroendocrine mechanisms, and they can regulate metabolism, adiposity, homoeostasis and energy balance, and central appetite and food reward signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 118 publications
(250 reference statements)
0
43
0
Order By: Relevance
“…Previous studies have demonstrated that the metabolites from the gut microbiota act as significant agents in a wide range of diseases, such as cancer, stroke, irritable bowel syndrome, and even mental disorders, including obesity [ 39 , 40 ]. In this study, we analyzed microbiota–substrate–metabolite–target (MSMT) networks and found that Lactobacillus paracasei JS1 , isoflavone, equol, and IL6 exhibited considerable connectivity in the networks, indicating significant antiobesity effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the metabolites from the gut microbiota act as significant agents in a wide range of diseases, such as cancer, stroke, irritable bowel syndrome, and even mental disorders, including obesity [ 39 , 40 ]. In this study, we analyzed microbiota–substrate–metabolite–target (MSMT) networks and found that Lactobacillus paracasei JS1 , isoflavone, equol, and IL6 exhibited considerable connectivity in the networks, indicating significant antiobesity effects.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of the microbial community within the gut has been linked with several metabolic diseases such as obesity, non-alcoholic fatty liver, cardiovascular disease, diabetes, osteoporosis and many other diseases. [26][27][28][29] Although gut microbiota posseses an essential role in the regulation of blood GLU. 17 Little has been reported the mechanism of the gut microbiota composition and gut barrier on blood glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SCFAs are thought to play essential roles in maintaining host energy homeostasis and insulin sensitivity. 29,45 Both Blautia and Coprococcus are metabolically enriched butyrate-producing bacteria. Butyric acid is essential for maintaining gut health, and it provides energy to intestinal cells and sends signals to the host.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight a new line of communication between the gut microbiota and the brain. Mounting evidence indicates that the gut microbiota might target the brain via a direct pathway of electrical stimulation of the vagus nerve and an indirect means involving an immune–neuroendocrine mechanism [ 66 ]. Torres-Fuentes et al [ 67 ] reviewed and discussed the role of the gut–brain axis in obesity.…”
Section: Obesity and Gut Microbiotamentioning
confidence: 99%